Implication of OTX2 in Pigment Epithelium Determination and Neural Retina Differentiation - Bovolenta, Paola (J Neurosci, 1997)
The expression pattern of Otx2, a homeobox-containing gene, was analyzed from the beginning of eye morphogenesis until neural retina differentiation in chick embryos. Early on, Otx2 expression was diffuse throughout the optic vesicles but became restricted to their dorsal part when the vesicles contacted the surface ectoderm. As the optic cup forms,Otx2 was expressed only in the outer layer, which gives rise to the pigment epithelium. This early Otx2expression pattern was complementary to that of PAX2, which localizes to the ventral half of the developing eye and optic stalk.Otx2 expression was always observed in the pigment epithelium at all stages analyzed but was extended to scattered cells located in the central portion of the neural retina around stage 22. The number of cells expressing Otx2 transcripts increased with time, following a central to peripheral gradient. Bromodeoxyuridine labeling in combination with immunohistochemistry with anti-OTX2 antiserum and different cell-specific markers were used to determine that OTX2-positive cells are postmitotic neuroblasts undergoing differentiation into several, if not all, of the distinct cell types present in the chick retina. These data indicate thatOtx2 might have a double role in eye development. First, it might be necessary for the early specification and subsequent functioning of the pigment epithelium. Later, OTX2 expression might be involved in retina neurogenesis, defining a differentiation feature common to the distinct retinal cell classes.